IMPLEMENTASI MUDARABAH PADA LEMBAGA KEUANGAN SYARIAH - Hatta, Muhammad (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2022)
The problems studied in this study are related to the implementation of Muḍārabah according to the Sharia Economic Law Compilation (KHES) and the Muḍārabah mechanism at Bank Syariah Indonesia Wonomulyo. This type of research is a qualitative research that builds meaning based on data obtained from the field. The procedure for this qualitative research is to process data which will produce descriptive data in the form of written and spoken words from people and observable behavior. Data was collected by conducting observations, in-depth interviews and documentation. Data analysis is done by giving meaning to the data that has been collected, then from the data a conclusion is drawn. The results of this study reveal that the implementation of muḍārabah in Islamic financial institutions, namely Bank Syariah Indonesia Wonomulyoakad muḍārabah has fulfilled and is in accordance with Islamic law and is contained in the Sharia Economic Law Compilation (KHES). At BSI KCP Wonomulyo, the application of muḍārabah contracts is only for collecting funds from customers, namely muārabah savings and muḍārabah deposits in distributing funds not being used. This is because the amount of risk that will be accepted by the BSI bank must bear all the losses experienced by the customer as a capital manager. Then the profit sharing or the ratio received must be based on an agreement between the two parties and will be received every month and within a predetermined period of time.